Molecular Exploitation of Apoptosis Pathways in Prostate Cancer. - Kyprianou, Natasha (Molecular medicine and medicinal chemistry., 2012)
This book focuses on the functional significance of targeting apoptosis for the treatment of prostate cancer. New concepts on the challenges relating to the development of resistance by androgen-independent tumors are introduced, in terms of the contribution of anoikis and cross-talk of androgens with key growth factor signaling pathways. This volume also provides insightful discussion on the exploitation of the apoptotic and angiogenic synergism towards complete eradication of prostate tumors. Last but not least, it includes reflections on the drug development challenge based on the analysis.